Design of Wireless Intelligent Video Surveillance System Based on 3G Network - Qigui Zhang; Yu Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Depending on the development of embedded technology and mobile communication network, an intelligent wireless video surveillance solution based on the 3G network and HI3515 is proposed in this paper. The front-end of the surveillance system is composed of Hi3515 and SIM5216E, which integrates intelligent video analysis, intelligent control, and other functions. It has realized only transferring the useful video surveillance information---abnormal event information, setting the special receiver that will receive the surveillance information, and transferring the surveillance information according to user's commands. Surveillance scene information database has been established on the video surveillance center. According to the surveillance video data received from the front-end of the surveillance system, the corresponding electronic map and the surrounding information can be obtained and multi-channel surveillance can be realized as well. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3909